2010
DOI: 10.3109/09553002.2010.484480
|View full text |Cite
|
Sign up to set email alerts
|

Protection against radiation-induced oxidative damage by an ethanolic extract ofNigella sativaL.

Abstract: The results obtained from the different experimental systems suggest the radioprotective ability of EE-NS involving prevention of radiation-induced oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
4
25
1
1
Order By: Relevance
“…This contrasts reports of increases in splenic ROS levels 24 h after exposure to 2 Gy [66]. Thymocytes isolated from mice 5-7 days after exposure to 1.5-3 Gy also had increased levels of ROS.…”
Section: Overall Impact Of Radiationcontrasting
confidence: 80%
“…This contrasts reports of increases in splenic ROS levels 24 h after exposure to 2 Gy [66]. Thymocytes isolated from mice 5-7 days after exposure to 1.5-3 Gy also had increased levels of ROS.…”
Section: Overall Impact Of Radiationcontrasting
confidence: 80%
“…Oral administration of N. sativa oil (1 ml/kg/day for 5 days/week) prior to irradiation considerably attenuated the irradiation-related biochemical, immunological, and pathological effects [41]. Along the same lines, Rastogi and colleagues demonstrated that an ex vivo treatment of mouse splenic lymphocytes with an ethanolic extract of N. sativa 1 h prior to irradiation prevented that the formation of lipid peroxides and intracellular ROS; factors that mediate radiation-induced DNA damage and apoptosis [42]. Furthermore, oral administration of an ethanolic extract of N. sativa (100 mg/kg/day for 5 days) protected irradiated Swiss albino mice against oxidative injury to the spleen and liver tissues in as measured by the activity of anti-oxidant enzymes and lipid peroxidation [42].…”
Section: Effects Of N Sativa On Inflammationmentioning
confidence: 90%
“…Along the same lines, Rastogi and colleagues demonstrated that an ex vivo treatment of mouse splenic lymphocytes with an ethanolic extract of N. sativa 1 h prior to irradiation prevented that the formation of lipid peroxides and intracellular ROS; factors that mediate radiation-induced DNA damage and apoptosis [42]. Furthermore, oral administration of an ethanolic extract of N. sativa (100 mg/kg/day for 5 days) protected irradiated Swiss albino mice against oxidative injury to the spleen and liver tissues in as measured by the activity of anti-oxidant enzymes and lipid peroxidation [42]. These radio-protective effects were attributed to the radical scavenging potential of N. sativa [42].…”
Section: Effects Of N Sativa On Inflammationmentioning
confidence: 92%
“…Moreover, radiation-induced DNA damage was prevented in splenocytes pre-treated with NS ethanolic extract 52 . The liver tissue total oxidant status, lipid hydroperoxide level, and oxidative stress index were increased in the irradiated rats compared to the control rats, while total antioxidant status and sulfhydryl (-SH) levels were significantly declined.…”
Section: Anti-oxidant Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 87%
“…It caused an increase in the activities of SOD, catalase (CAT) and glutathione peroxidase (GPX) 51 . Also, NS had radio-protective effects against radiation-related oxidative stress and NS treatment meaningfully antagonized the effects of radiation; therefore, NS may be a beneficial agent in protection against ionizing radiationrelated tissue injury 52 . Ex-vivo treatment of mouse splenic lymphocytes with an ethanolic extract of NS before irradiation showed significant inhibition of the formation of lipid-peroxides and intracellular reactive oxygen species (ROS), which correlated with radiation-induced apoptosis.…”
Section: Anti-oxidant Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 99%